2021
DOI: 10.3390/su131810394
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Socially Assistive Robots in the Care of Older People: To Assist in Cognitive Training, to Remind or to Accompany?

Abstract: The rapid development of new technologies has caused interest in the use of socially assistive robots in the care of older people. These devices can be used not only to monitor states of health and assist in everyday activities but also to counteract the deterioration of cognitive functioning. The aim of the study was to investigate the attitudes and preferences of Polish respondents towards interventions aimed at the preservation/improvement of cognitive functions delivered by a socially assistive robot. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…e influence of gender on technology acceptance remains uncertain. However, women showed a more positive attitude towards SARs than men and had a significantly higher perception of the roles of robots in reminding about medications, meal times, and drinks [44]. Two studies reported insignificant differences in attitudes towards SARs, regardless of gender [20,41].…”
Section: Technology Acceptance Eory Modelsmentioning
confidence: 91%
“…e influence of gender on technology acceptance remains uncertain. However, women showed a more positive attitude towards SARs than men and had a significantly higher perception of the roles of robots in reminding about medications, meal times, and drinks [44]. Two studies reported insignificant differences in attitudes towards SARs, regardless of gender [20,41].…”
Section: Technology Acceptance Eory Modelsmentioning
confidence: 91%
“…The collection of potential end-users' opinions about older persons' robot-related needs and requirements was part of the project. We previously presented the findings of quantitative experiments that used the Users' Needs, Requirements, and Abilities Questionnaire (UNRAQ)-a mixedmethodology tool developed as a component of the research project [82][83][84][85][86][87][88][89][90][91][92][93][94].…”
Section: Methodsmentioning
confidence: 99%
“…In the situation of a demographic crisis, service robots can increase labor productivity and service quality [11]. They can also help elders' cognitive training and physical activities [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%